Iron core/shell nanoparticles as magnetic drug carriers: possible interactions with the vascular compartment. (September 2011) - Herrmann, Inge K; Urner, Martin; Hasler, Melanie; Roth-Z'Graggen, Birgit; Aemisegger, Caroline; Baulig, Werner; Athanassiou, Evagelos K; Regenass, Stephan; Stark, Wendelin J; Beck-Schimmer, Beatrice
Aims: Nanomagnets with metal cores have recently been shown to be promising candidates for magnetic drug delivery due to higher magnetic moments compared with commonly used metal oxides. Successful application strongly relies on a safe implementation that goes along with detailed knowledge of interactions and effects that nanomagnets might impart once entering the body.Materials & Methods: In this work, we put a particular focus on the interactions of ultra-strong metal nanomagnets (≥ three-times higher in magnetization compared with oxide nanoparticles) within the vascular compartment. Individual aspects of possible effects are addressed, including interactions with the coagulation cascade, the complement system, phagocytes and toxic or inflammatory reactions both by blood and endothelial cells in response to nanomagnet exposure.Results: We show that carbon-coated metal nanomagnets are well-tolerated by cells of the vascular compartment and have only minor effects on blood coagulation.Conclusion: These findings provide the fundament to initiate successful first in vivo evaluations opening metal nanomagnets with improved magnetic properties to fascinating applications in nanomedicine.